1992
DOI: 10.1177/002221949202500407
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depressive Symptoms in Children with Learning Disabilities

Abstract: Learning difficulties have been considered to be a symptom of childhood depression by some authors, whereas others have examined depression as a cause of cognitive difficulties, including learning disabilities (LD). This study examined the prevalence of depressive symptoms in a sample of public school elementary children aged 8 through 11, 37 boys and 16 girls, identified as LD by state standards. Of the sample of 53 children, 35.85% scored in the depressed range on the Children's Depression Inventory. Compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
1
22

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 36 publications
3
33
1
22
Order By: Relevance
“…In addition, the correlation between depression and these cognitive-behavioral factors tended to be higher for LD than NLD students. The observed association between depression and cognitive-behavioral factors is consistent with research on LD children and adolescents (Dalley et al, 1992;Hall & Haws, 1989;Kaff, 1988;Maag & Behrens, 1989;Stevenson & Romney, 1984;Wright-Strawderman & Watson, 1992). It also provides further support for models based on the association between depression and both cognitive and behavioral factors (Beck, 1972;Lewinsohn, 1974;Peterson et al, 1982).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In addition, the correlation between depression and these cognitive-behavioral factors tended to be higher for LD than NLD students. The observed association between depression and cognitive-behavioral factors is consistent with research on LD children and adolescents (Dalley et al, 1992;Hall & Haws, 1989;Kaff, 1988;Maag & Behrens, 1989;Stevenson & Romney, 1984;Wright-Strawderman & Watson, 1992). It also provides further support for models based on the association between depression and both cognitive and behavioral factors (Beck, 1972;Lewinsohn, 1974;Peterson et al, 1982).…”
Section: Discussionsupporting
confidence: 81%
“…Stevenson and Romney (1984) reported that 14% of a group of 103 LD children aged 8 to 13 years met the criterion for clinical depression on a self-report measure. Similarly, Wright-Strawderman and Watson (1992) found that 35.83% of a sample of 53 LD children aged 8 to 11 years met the clinical criterion on a self-report measure of depression. Kaff (1988) found that a group of 40 LD children displayed higher levels of depressed mood than a matched group of NLD children.…”
mentioning
confidence: 88%
“…On the other side, school difficulties and frustrations can trigger sad affects and depression. Learning disorders have been frequently associated with depressive symptomatology, which is many times higher in learning-disabled subjects than in normal controls [16,17]; depressive feelings are strongly connected with cognitive and metacognitive functioning [18,19]. However, negative self-perceptions can be found in normally achieving students [20].…”
Section: Discussionmentioning
confidence: 99%
“…Essas diferenças podem ser em decorrência de vários fatores como diferentes instrumentos diagnósticos utilizados, local do estudo (em residências ou escolas), população estudada (amostra ou população total). Além disso, o transtorno depressivo pode ser subdiagnosticado dado a sua similaridade com outros transtornos assim como a presença de comorbidades, como TDAH, transtornos de ansiedade, de conduta, agressividade, que podem persistir após cessar o episódio depressivo 44 . Já os transtornos ansiosos são os quadros psiquiátricos mais comuns tanto em crianças quanto em adultos, com uma prevalência em crianças e adolescentes estimada em torno de 9% 45 .…”
Section: Características Dos Estudosunclassified